ATIM-12. NEOADJUVANT ANTI-PD-1 IMMUNOTHERAPY PROMOTES INTRATUMORAL AND SYSTEMIC IMMUNE RESPONSES IN RECURRENT GLIOBLASTOMA: AN IVY CONSORTIUM TRIAL. (5th November 2018) - Prins, Robert; Mochizuki, Aaron; Orpilla, Joey; Lee, Alexander; Davidson, Tom; Gaffey, Sarah; Sanders, Catherine; Rytlewski, Julie; Ellingson, Benjamin; Li, Gang; Yong, William; Clarke, Jennifer; et al.
Abstract: Glioblastoma is the most common malignant brain tumor in adults and is associated with poor survival. It is often resistant to standard-of-care chemotherapy and radiation, necessitating the development of more effective treatments. The Ivy Foundation Early Phase Clinical Trials' Consortium conducted a randomized, multi-institution clinical trial to evaluate the immune response and survival following neoadjuvant and adjuvant therapy with pembrolizumab, a PD-1 monoclonal antibody, in thirty patients with recurrent, surgically resectable glioblastoma. Patients who received neoadjuvant pembrolizumab, with continued adjuvant therapy following surgery, had significantly extended overall survival compared to patients that received adjuvant, post-surgical PD-1 blockade alone (HR=0.33, p<0.008, log-rank test). Survival was directly associated with an elevated IFN-g gene expression signature in the tumor, but only in patients who received neoadjuvant PD-1 blockade (HR=0.15, p<0.02, Wald test). Focal induction of PD-L1 in the tumor microenvironment was observed in the neoadjuvant group and linked with the IFN-g gene expression signature and extended survival. Similarly, neoadjuvant pembrolizumab was associated with expanded T cell receptor clones, increased markers of activation in CD8+ T cells that expressed PD-1, and a decreasing monocytic population in the peripheral blood (p<0.03, two-sided t-test). These findings suggest that the neoadjuvant timing of PD-1 blockade enhances the local and systemic immune response, and may represent a more efficacious approach to the treatment of this uniformly lethal brain tumor.